Autonomous movable packrat for habitual chores - Sheeba Rachel, S; Azhagumeena, S; Rajakumari, S; Madhumidha, A (International Journal of Engineering and Technology, 2018)
Internet of Things (IoT) and artificial intelligence (AI) can play a major role in improving the way we live. Improvement in quality of life can be achieved by connecting devices. Thus we present a waste collection solution based on providing intelligence to waste bins, using an IoT prototype with sensors. Here we provide with an autonomous intelligent system that moves automatically when it detects waste. We use kinetic sensor that identifies the trash and help the robot in picking it. It can read, collect, analyze the trash collected and report the user about the facts such as the time at which the more amount of waste get collected and the kind of waste which gets accumulated large in number. Such data, when put into a spatio-temporal context and processed by intelligent and optimized algorithms, can be used to dynamically manage waste collection mechanisms. In addition to the above the unique characteristic of the robot is that it can recognize humans..
Keywords: Internet of Things (LoT); Artificial Intelligence (AI); Kinetic Sensor.